Decoupage as an art therapy technique in human functioning in late adulthood. - Miłek, Katarzyna; Figaj, Magdalena (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The article presents research on the use of decoupage as an art therapy technique among the residents of a social welfare home. The technique used here is described along with its location in the history of art therapy. The author establishes the definition, goals and functions that this field of therapy fulfills in human life, with particular focus on the impact in late adulthood. The research was conducted in the Nursing Home in Gniezno on the basis of an interview questionnaire and a survey conducted among seniors living in the Social Welfare Home. The research was preceded by conducting classes using the decoupage technique.